PERAN IKLIM KERJA ORGANISASI DAN KOMPETENSI KERJA TERHADAP KINERJA KARYAWAN DINAS KESEHATAN KABUPATEN NGADA PROVINSI NTT - , LIDWINA DHIU, IJK Sito Meiyanto, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aimed to comprehend the role of organization work climate and competence toward employee performance. The subject of this research consisted of 60 persons who have been working as employee at Health Service of Ngada District. The data collection used three scales of organization work climate, competence scale, and scale of employee performance. The result of multiple regression analysis indicated that the organization work climate and comptence altogether could become a predictor to estimate the performance 27,05% by (r) square 0,270 (p=0,000). Organization work climate could be a performance predictor by effective contribution value 14,14% (p=0,002). Work competence could be used as a predictor toward the performance by the effective contribution 12,91% (p=0,003).